Conceptual-methodological aspects in the formation of intercultural competence to pupils in secondary classes - Roxana DOROBANTU-DINA (Acta et Commentationes, Sciences of Education, 2022)
This article summarizes the conceptual-methodological aspects that are the basis for the formation of intercultural competence for secondary school students. The curricular approach to intercultural education is a relatively new field for Romania. More specifically, from the 2017-2018 school year it is studied in secondary classes, in this case in the sixth grade, one hour a week in the common trunk. In 2016, the new framework curricula for the secondary were adopted, approved by the order of the Minister of National Education and Scientific Research no. 3590 / 05.04.2016. These are applied from the 2017-2018 school year to the 5th and 6th grades, starting with the 2019-2020 school year to the 7th grade, and from the 2020-2021 school year to the 8th grade. The purpose of school education is based on the acquisition of key competencies by students and the formation of the profile of the graduate, able to integrate socially and professionally. One of the eight key competences contained in the 2006 Council of Europe Recommendation is the intercultural competence. In essence, intercultural competence is formed within several disciplines of study, but not only at the level of intercultural education. Thus, we claim that it is "polished" in an organized and systematic way through formal and non-formal activities by teachers. A series of teaching methods are the basis for the formation of intercultural competence in secondary school students are mentioned here. These have been successfully applied by the author in the classroom.